If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2b + 1) + (11b + -7) = 0 Reorder the terms: -5(1 + 2b) + (11b + -7) = 0 (1 * -5 + 2b * -5) + (11b + -7) = 0 (-5 + -10b) + (11b + -7) = 0 Reorder the terms: -5 + -10b + (-7 + 11b) = 0 Remove parenthesis around (-7 + 11b) -5 + -10b + -7 + 11b = 0 Reorder the terms: -5 + -7 + -10b + 11b = 0 Combine like terms: -5 + -7 = -12 -12 + -10b + 11b = 0 Combine like terms: -10b + 11b = 1b -12 + 1b = 0 Solving -12 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1b = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 1b = 0 + 12 1b = 0 + 12 Combine like terms: 0 + 12 = 12 1b = 12 Divide each side by '1'. b = 12 Simplifying b = 12
| -1=5+n | | 72=3x(x+2) | | 1.3q-3.8-5.6q=-5.3q-4.3 | | 130=10x+7y | | -14=-7m | | 4+9y-3=7y+43-4y | | 729p^2-36= | | .49x^2+12x=20 | | 15+10x+x^2=0 | | -21/4(-10)+80 | | 2h+1=-17 | | -10=10a | | 18x-12=22x+8 | | 3k=-12 | | 8-5x=-22 | | 8-5x=-22 | | 12.5*n=100 | | 4x^3-9x^2-x-6=0 | | -21/4(-10) | | 31=-7+x | | -21/4(10) | | 2(x+22)=5+3(x-2)-4x | | -3x8+4/(-2) | | r-45=-45 | | 9g+11=-2 | | 4xy^2+44x^2y^2-28xy^2=0 | | 3/4w=-16/27 | | 3/4s=-16/27 | | -16t^2+16=0 | | ab-9a+4b-36= | | -5(-3u+7)-3u=6(u-6)-7 | | -3=k+2 |